Analisis Kualitas Aplikasi Layanan Aspirasi Dan Pengaduan Online Rakyat (LAPOR) Menggunakan Metode Webqual 4.0 - Habiburrahman Al Farisi; Reza Ade Putra (LPPM Universitas Putera Batam, 2025)
The People's Online Aspiration and Complaint Service (LAPOR) is a digital media provided by the government to bridge two-way communication between the public and government agencies. In order to support transparency and responsive public services, the quality of the LAPOR website is an important factor that needs to be evaluated periodically. This internship aims to analyze the quality of the LAPOR South Sumatra website based on the Webqual 4.0 approach which includes three main dimensions, namely Usability, Information Quality, and Service Interaction Quality. This study uses a quantitative method with a descriptive approach. Data were obtained by distributing questionnaires to active users of the LAPOR website, with instruments designed referring to indicators in the Webqual 4.0 model. Data analysis was carried out to measure user perceptions of the website quality, as well as to identify aspects that still need improvement. The results of the analysis show that the quality of the LAPOR South Sumatra website is generally in the good category with an average score of 3.80 for usability, 3.72 for information quality, and 3.65 for service interaction quality, especially in the Information Quality dimension. These findings are expected to serve as evaluative material for website managers in order to continuously improve the quality of digital services..